Ultrasound-responsive oxygen vacancy strontium titanate-titanium carbide composite nanohydrogel for treating intervertebral disc degeneration
Patent Information
- Application Number
- CN202611173093.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-04
- Publication Date
- 2026-10-13
AI Technical Summary
[0007]本发明旨在提供一种负载氧空位钛酸锶-碳化钛复合材料的超声响应可注射水凝胶,以解决现有椎间盘退变治疗中局部递送效率低、ROS清除不足、炎症通路调控有限和细胞外基质保护不足的问题;通过水凝胶实现材料在椎间盘局部滞留,通过SrTiOv-TiCx的氧空位和超声响应特性增强ROS清除及NF-κB/MAPK炎症通路调控,从而保护髓核细胞、抑制ECM降解并延缓椎间盘退变
1.本发明构建了SrTiOv-TiCx氧空位复合结构。
Smart Images

Figure CN122894504A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of biomedical materials and tissue engineering technology, specifically to the application of ultrasound-responsive oxygen-vacancy strontium titanate-titanium carbide composite nanohydrogels in the treatment of intervertebral disc degeneration. Background Technology
[0002] Currently, commonly used clinical treatments include analgesics, anti-inflammatory drugs, physical therapy, intradiscal injections, and surgical intervention. While these methods are effective in relieving pain and improving short-term symptoms, most primarily address symptoms and fail to address the core pathological microenvironment of intervertebral disc degeneration, thus hindering the sustained regulation of excessive ROS accumulation, inflammatory cascades, and extracellular matrix degradation. In particular, drug therapy suffers from issues such as low local drug accessibility, systemic distribution, rapid metabolism, and insufficient local maintenance time, making it difficult to achieve long-term effective therapeutic concentrations in the low-blood-supply, low-metabolic intervertebral disc.
[0003] Hydrogel materials typically function primarily as physical fillers or carriers. They have limited ability to actively scavenge excess ROS in degenerated microenvironments, insufficient ability to regulate inflammatory signaling pathways such as NF-κB / MAPK, and difficulty in simultaneously achieving antioxidant, immunomodulatory, and extracellular matrix protection.
[0004] Some antioxidant nanomaterials or enzyme-like materials have been used to scavenge ROS and improve the inflammatory microenvironment, but these materials still have certain shortcomings: First, some materials mainly rely on their own passive antioxidant properties and lack external stimulus response regulation, making it difficult to enhance the therapeutic effect according to the needs of the lesion site; Second, some materials only focus on ROS scavenging and fail to further synergistically regulate inflammatory signaling pathways and immune cell phenotypic transformation; Third, when nanomaterials are administered alone, there may be problems such as insufficient local retention, easy diffusion, uncontrollable release, or unstable distribution after injection; Fourth, the antioxidant, anti-inflammatory, and tissue repair functions of some materials are mutually exclusive, making it difficult to form a continuous intervention targeting the pathological chain of intervertebral disc degeneration.
[0005] Piezoelectric or ultrasound-responsive materials have certain application potential in the field of tissue repair. Ultrasound, as a relatively non-invasive and deeply penetrating exogenous stimulation method, can be used to activate piezoelectric materials and enhance their electron transfer or catalytic properties. However, the application of existing ultrasound-responsive materials in the treatment of intervertebral disc degeneration still has shortcomings. For example, there is a lack of effective integration between the material structure design and ROS adsorption sites, resulting in limited ROS regulation efficiency after ultrasound activation; single piezoelectric materials are prone to electron-hole recombination, affecting catalytic or antioxidant efficiency; at the same time, their integration with injectable hydrogel delivery systems is insufficient, making it difficult for the material to be stably retained locally in the degenerated intervertebral disc and exert a sustained effect.
[0006] In summary, while existing technologies have covered areas such as drug therapy, hydrogel delivery, antioxidant nanomaterials, and ultrasound-responsive materials, a comprehensive therapeutic system is still lacking that can stably deliver drugs locally to the intervertebral disc, respond to ultrasound stimulation, actively clear ROS, regulate the NF-κB / MAPK inflammatory pathway, promote macrophage polarization from M1 to M2, and further protect nucleus pulposus cells and the extracellular matrix. Therefore, the application of ultrasound-responsive oxygen-vacancy strontium titanate-titanium carbide composite nanohydrogel in the treatment of intervertebral disc degeneration is proposed. Summary of the Invention
[0007] This invention aims to provide an ultrasound-responsive injectable hydrogel of SrTiOv-TiCx composite material with oxygen vacancies, to address the problems of low local delivery efficiency, insufficient ROS clearance, limited inflammatory pathway regulation, and insufficient extracellular matrix protection in existing treatments for intervertebral disc degeneration. The hydrogel allows for local retention of the material in the intervertebral disc, and the oxygen vacancies and ultrasound-responsive properties of SrTiOv-TiCx enhance ROS clearance and NF-κB / MAPK inflammatory pathway regulation, thereby protecting nucleus pulposus cells, inhibiting ECM degradation, and delaying intervertebral disc degeneration.
[0008] To achieve the above-mentioned objectives, the present invention provides the following technical solution: an ultrasonically responsive oxygen-vacancy strontium titanate-titanium carbide composite material, wherein the composite material is a SrTiOv-TiCx composite structure, composed of oxygen-vacancy strontium titanate SrTiOv and titanium carbide TiCx; wherein SrTiOv possesses oxygen vacancy active sites, and SrTiOv and TiCx form a heterogeneous interface structure; the composite material exhibits ultrasonic response characteristics and controllable ROS regulation capability.
[0009] As a preferred embodiment of the present invention, the mass ratio of SrTiOv to TiCx is 10:1 to 1:10, preferably 2:1 to 1:2; the particle size of the composite material is 20 to 500 nm, preferably 50 to 300 nm; the composite material can enhance interfacial electron transfer, inhibit electron-hole recombination, and improve ROS adsorption and removal efficiency under ultrasonic stimulation.
[0010] As a preferred embodiment of the present invention, the hydrogel formulation uses sodium alginate-chitosan as the hydrogel matrix and loads the SrTiOv-TiCx composite material as described in claim 1 or 2; the proportions of each component satisfy: final concentration of SrTiOv-TiCx 1-1000 μg / mL, sodium alginate 0.5%-5% w / v, and chitosan 0.1%-3% w / v; the gelation time of the hydrogel formulation is 10 s-10 min.
[0011] As a preferred embodiment of the present invention, the final concentration of SrTiOv-TiCx is preferably 100 μg / mL, the concentration of sodium alginate is preferably 1.5% to 2.5% w / v, the concentration of chitosan is preferably 0.5% to 1.5% w / v, and the gelation time of the hydrogel formulation is 2 min under optimized conditions; the mass ratio of sodium alginate to chitosan is 10:1 to 1:5, preferably 3:1 to 1:1.
[0012] As a preferred embodiment of the present invention, the hydrogel formulation further comprises a crosslinking agent and a physiologically acceptable solvent; the concentration of the crosslinking agent is 1-500 mmol / L, and is selected from one or more of calcium chloride, calcium gluconate, calcium sulfate, sodium β-glycerophosphate, and sodium tripolyphosphate; the physiologically acceptable solvent is one or more of deionized water, PBS buffer, physiological saline, and weakly acidic aqueous solution.
[0013] The preparation method of ultrasound-responsive oxygen-vacancy strontium titanate-titanium carbide composite nanohydrogel includes the following steps: S1, preparation of oxygen-vacancy strontium titanate SrTiOv: a precursor is prepared by mixing a strontium source and a titanium source, strontium titanate is prepared by hydrothermal method / sol-gel method / calcination method, and oxygen vacancies are constructed by reduction heat treatment to obtain SrTiOv; S2. Preparation of a uniform TiCx dispersion: TiCx material is added to a physiological solvent and dispersed by ultrasonication to obtain a stable TiCx dispersion; S3. Preparation of SrTiOv-TiCx composite material: SrTiOv and TiCx dispersion were mixed in proportion, stirred, ultrasonically compounded, centrifuged, washed and dried to obtain SrTiOv-TiCx composite material; S4. Preparation of sodium alginate-chitosan composite precursor solution: Dissolve sodium alginate and chitosan separately, adjust the pH and mix them in proportion to obtain hydrogel precursor solution. S5. Loading and cross-linking: The SrTiOv-TiCx composite material is added to the precursor solution and dispersed evenly. A cross-linking agent is added for cross-linking, and the mixture is rapidly molded to obtain an injectable composite hydrogel formulation.
[0014] As a preferred embodiment of the present invention, in step S1, the heat treatment temperature is 300–900℃, the heat treatment time is 0.5–12h, and the heat treatment atmosphere is an inert atmosphere, a low-oxygen atmosphere, or a reducing atmosphere; in step S2, the concentration of the TiCx dispersion is 0.1–20 mg / mL, and the ultrasonic dispersion time is 5–120 min; in step S3, the composite reaction time is 0.5–48 h, and the centrifugation speed is 3000–15000 rpm.
[0015] Ultrasound-responsive oxygen-vacancy strontium titanate-titanium carbide composite nanohydrogels are used in the treatment of intervertebral disc degeneration to prepare drugs, injectable medical preparations, sustained-release preparations, or intervertebral disc tissue repair materials for treating or repairing intervertebral disc degeneration.
[0016] As a preferred technical solution of the present invention, the composite material or composite hydrogel preparation achieves targeted therapeutic intervention under the action of ultrasound. The specific mechanism of action includes: clearing excess ROS in the intervertebral disc degeneration microenvironment, regulating the NF-κB / MAPK inflammatory signaling pathway, and reducing the expression of P65, p-P65, MMP13, and NLRP3 proteins.
[0017] As a preferred technical solution of the present invention, the composite material or composite hydrogel preparation achieves the repair effects of macrophage M1-to-M2 polarization, nucleus pulposus cell protection, ECM degradation inhibition, and delaying the progression of intervertebral disc degeneration by regulating the inflammatory microenvironment.
[0018] Compared with the prior art, the beneficial effects of the present invention are as follows: 1. This invention constructs an SrTiOv-TiCx oxygen-vacancy composite structure.
[0019] SEM, TEM, mapping, and XPS results confirmed that SrTiOv nanoparticles can be stably bonded to the TiCx surface to form a composite heterostructure. The particle size of the material is about 200 nm, and the lattice spacing of the strontium titanate 001 crystal plane is about 0.276 nm, which provides a structural basis for the stability and functionality of the material.
[0020] 2. This invention improves the ultrasonic response and ROS regulation capability of the material.
[0021] The band gap of the SrTiOv-TiCx composite decreased from 1.66 eV for SrTiOv to 0.13 eV; the oxygen adsorption energy further decreased from -2.30 eV for SrTiOv and -3.73 eV for TiCx to -4.92 eV for SrTiOv-TiCx, indicating that the composite material has stronger oxygen / ROS adsorption capacity and ultrasonic response potential.
[0022] 3. This invention can inhibit inflammatory pathways and matrix degradation.
[0023] Western blot (WB), ROS staining, and MMP13 detection results showed that ST could reduce ROS levels under ultrasound and decrease the expression of inflammation and matrix degradation-related factors such as P65, p-P65, MMP13, and NLRP3, indicating that it can exert anti-inflammatory and ECM protective effects through the ROS / NF-κB related pathway.
[0024] 4. This invention has good biocompatibility.
[0025] CCK-8 results showed that SrTiOv-TiCx had almost no cytotoxicity after being co-cultured with nucleus pulposus cells at a concentration of 100 ppm for 24 h; HE staining of major organs, blood routine and blood biochemistry results showed that the material and hydrogel had no obvious in vivo toxicity.
[0026] 5. This invention has good injectability and rapid gelation properties.
[0027] Sodium alginate-chitosan hydrogel loaded with 100 ppm ST can rapidly solidify within 2 minutes at room temperature, which is beneficial for local injection into the intervertebral disc and material retention.
[0028] 6. This invention can slow down the progression of intervertebral disc degeneration.
[0029] In animal experiments, after ST hydrogel combined with ultrasound treatment, micro-CT showed that the treatment group was significantly improved compared with the model group. MRI showed that the hydrogel did not affect the bone structure. HE, safranin O and immunohistochemical results further confirmed its effect on intervertebral disc degeneration repair.
[0030] The difference between this patented solution and existing technologies lies in the fact that this solution does not use a single drug, ordinary hydrogel, or single antioxidant nanomaterial to treat intervertebral disc degeneration. Instead, it loads SrTiOv-TiCx composite nanomaterials with oxygen vacancy structures into an injectable sodium alginate-chitosan hydrogel, constructing a composite therapeutic system that can be locally injected, rapidly gelled, and activated by ultrasound. Its key technical features are: the oxygen vacancies in SrTiOv-TiCx provide ROS adsorption sites; SrTiOv and TiCx form a heterogeneous interface to promote electron transfer and enhance ultrasound response performance; and the sodium alginate-chitosan hydrogel improves the material's retention and sustained-release capacity in the intervertebral disc. These features work together to enable this solution to reduce ROS levels under ultrasound, inhibit the TNF-α / NF-κB / MAPK inflammatory pathway, and reduce the expression of factors such as P65, p-P65, MMP13, and NLRP3, thereby protecting nucleus pulposus cells, inhibiting extracellular matrix degradation, and delaying intervertebral disc degeneration. Attached Figure Description
[0031] Figure 1 This is a schematic diagram of the structure provided by the present invention. Detailed Implementation
[0032] To make the objectives, technical solutions, and advantages of the embodiments of the present invention clearer, the technical solutions of the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments.
[0033] Therefore, the following detailed description of the embodiments of the present invention is not intended to limit the scope of the claimed invention, but merely illustrates some embodiments of the invention. All other embodiments obtained by those skilled in the art based on the embodiments of the present invention without inventive effort are within the scope of protection of the present invention. It should be noted that, in the absence of conflict, the embodiments and features and technical solutions in the embodiments of the present invention can be combined with each other. It should be noted that similar reference numerals and letters in the following figures indicate similar items; therefore, once an item is defined in one figure, it does not need to be further defined and explained in subsequent figures.
[0034] Example 1: Application of ultrasound-responsive oxygen-vacancy strontium titanate-titanium carbide composite nanohydrogel in the treatment of intervertebral disc degeneration. 1. Preparation of SrTiO2 nanomaterials. Weigh out the strontium source and titanium source, and add them to deionized water or a water / ethanol mixed solvent at a molar ratio of Sr to Ti of 1:1. Stir magnetically for 30 to 60 minutes to ensure thorough mixing and obtain the strontium titanate precursor solution.
[0035] The precursor solution was transferred to a reaction vessel and reacted at 120–200 °C for 6–24 h. After the reaction, the mixture was allowed to cool naturally to room temperature. The resulting precipitate was washed with deionized water and ethanol, collected by centrifugation, and dried to obtain strontium titanate precursor particles.
[0036] The obtained strontium titanate precursor particles were placed in a tube furnace and heat-treated under nitrogen, argon or low oxygen atmosphere at a temperature of 400–800 °C for 1–6 h to obtain oxygen-vacancy strontium titanate SrTiOv nanomaterials with oxygen vacancy structure.
[0037] In this step, the heat treatment is used to form oxygen vacancy structures in the strontium titanate material. Oxygen vacancies can serve as adsorption and reaction sites for reactive oxygen species, thereby enhancing the material's ability to regulate excessive ROS in the microenvironment of degenerated intervertebral discs.
[0038] 2. Preparation of TiCx dispersion Weigh the TiCx material and add it to deionized water or PBS buffer to prepare a TiCx dispersion of 1–5 mg / mL.
[0039] The dispersion was placed in an ultrasonic disperser and ultrasonically treated for 10–60 min to uniformly disperse TiCx, thus obtaining a TiCx dispersion.
[0040] Among them, TiCx can be titanium carbide nanosheets, Ti3C2Tx MXene or other titanium carbide materials. Its role is to construct a conductive interface and promote the interfacial electron transfer of SrTiOv-TiCx composite material under ultrasonic stimulation.
[0041] 3. Preparation of SrTiOv-TiCx composite materials The SrTiOv nanomaterial obtained in step 1 is added to the TiCx dispersion obtained in step 2, so that the mass ratio of SrTiOv to TiCx is 1:1.
[0042] The mixture was magnetically stirred at room temperature for 12 h and then ultrasonically dispersed for 10–30 min to ensure that the SrTiOv nanoparticles were fully bonded to the TiCx surface.
[0043] After the reaction was completed, the mixture was centrifuged at 8000–12000 rpm for 10–20 min, and the supernatant was discarded. The precipitate was washed 2–3 times with deionized water, and then freeze-dried or vacuum-dried to obtain the SrTiOv-TiCx composite material.
[0044] In the obtained SrTiOv-TiCx composite material, SrTiOv provides oxygen vacancies and a piezoelectric response basis, while TiCx promotes interfacial electron transfer. The two form a heterostructure, which can enhance the ROS adsorption and scavenging ability under ultrasonic response.
[0045] 4. Preparation of sodium alginate solution Weigh out sodium alginate and add it to PBS buffer to prepare a sodium alginate solution with a mass-volume concentration of 2% w / v.
[0046] Place it at room temperature and stir magnetically for 2–12 hours until the sodium alginate is completely dissolved to obtain a transparent or homogeneous sodium alginate solution.
[0047] 5. Preparation of chitosan solution Weigh out chitosan and add it to a 0.5%–1% acetic acid aqueous solution to prepare a chitosan solution with a mass-volume concentration of 1% w / v.
[0048] Stir the mixture at room temperature for 4–12 h to completely dissolve the chitosan. Then adjust the pH to 6.0–7.2 using NaOH solution to obtain a chitosan solution.
[0049] 6. Preparation of composite hydrogel precursor solution Mix 2% w / v sodium alginate solution and 1% w / v chitosan solution at a volume ratio of 1:1, and vortex or mechanically stir for 5–30 min to obtain sodium alginate-chitosan composite hydrogel precursor solution.
[0050] 7. Loading of SrTiOv-TiCx The SrTiOv-TiCx composite material obtained in step 3 was added to the hydrogel precursor solution obtained in step 6 to make the final concentration of SrTiOv-TiCx 100 μg / mL, i.e. 100 ppm.
[0051] The system was vortexed for 1–5 min and then dispersed under low-power ultrasonic conditions for 1–3 min to ensure that SrTiOv-TiCx was uniformly dispersed in the sodium alginate-chitosan hydrogel precursor solution.
[0052] 8. Crosslinking into gel A cross-linking agent is added to the above-mentioned hydrogel precursor solution to induce a cross-linking reaction, forming an injectable composite hydrogel of sodium alginate-chitosan loaded with SrTiOv-TiCx.
[0053] The cross-linking agent can be calcium chloride, calcium gluconate, or calcium sulfate, with a concentration of 20–100 mmol / L.
[0054] In this embodiment, the composite hydrogel loaded with 100 μg / mL SrTiOv-TiCx can gel within about 2 minutes at room temperature.
[0055] The resulting hydrogel has injectability, local retention and ultrasonic response properties, and can be used for local delivery of SrTiOv-TiCx composite materials to the intervertebral disc.
[0056] Example 2: Application of ultrasound-responsive oxygen-vacancy strontium titanate-titanium carbide composite nanohydrogel in the treatment of intervertebral disc degeneration. This composite hydrogel uses sodium alginate and chitosan as the hydrogel matrix and oxygen-vacancy strontium titanate-titanium carbide composite material SrTiOv-TiCx as the functional nanocomponent. Through cross-linking, an injectable, locally depositable composite hydrogel system with ultrasound-responsive function is formed. After injection into the degenerated intervertebral disc, this system can enhance the adsorption and scavenging capacity of SrTiOv-TiCx for reactive oxygen species under ultrasound, reduce the oxidative stress level in the degenerated microenvironment, and further regulate the NF-κB / MAPK inflammation-related signaling pathway, reducing the expression of inflammatory factors and extracellular matrix degradation-related factors, thereby protecting nucleus pulposus cells, inhibiting extracellular matrix degradation, and delaying the progression of intervertebral disc degeneration.
[0057] I. The ultrasound-responsive injectable composite hydrogel of the present invention comprises the following components: The composite material consists of oxygen-vacancy strontium titanate-titanium carbide (SrTiOv-TiCx), sodium alginate, chitosan, a crosslinking agent, and a physiologically acceptable solvent. SrTiOv-TiCx is a functional nanomaterial used to regulate the level of reactive oxygen species in the degenerated intervertebral disc under ultrasound and participate in the regulation of the inflammatory microenvironment. Sodium alginate and chitosan form an injectable hydrogel network to improve the retention and sustained-release properties of SrTiOv-TiCx in the intervertebral disc. The crosslinking agent induces hydrogel formation. The physiologically acceptable solvent dissolves or disperses the above components.
[0058] The final concentration of SrTiOv-TiCx in the hydrogel is 1–1000 μg / mL, preferably 10–500 μg / mL, more preferably 50–200 μg / mL, and most preferably 100 μg / mL.
[0059] The sodium alginate in the hydrogel has a mass-volume concentration of 0.5% to 5% w / v, preferably 1% to 3% w / v, and more preferably 1.5% to 2.5% w / v.
[0060] The chitosan concentration in the hydrogel is 0.1% to 3% w / v, preferably 0.3% to 2% w / v, and more preferably 0.5% to 1.5% w / v.
[0061] The mass ratio of sodium alginate to chitosan is 10:1 to 1:5, preferably 5:1 to 1:2, and more preferably 3:1 to 1:1.
[0062] The concentration of the crosslinking agent is 1–500 mmol / L, preferably 10–200 mmol / L, and more preferably 20–100 mmol / L. The crosslinking agent includes, but is not limited to, one or more of calcium chloride, calcium gluconate, calcium sulfate, sodium β-glycerophosphate, and sodium tripolyphosphate.
[0063] Physiologically acceptable solvents include, but are not limited to, deionized water, PBS buffer, physiological saline, weakly acidic aqueous solutions, or combinations thereof.
[0064] II. Structural Characteristics of Functional Nanomaterial SrTiOv-TiCx The SrTiOv-TiCx described in this invention is formed by combining oxygen-vacancy strontium titanate (SrTiOv) and titanium carbide (TiCx). SrTiOv possesses an oxygen-vacancy structure, which can serve as adsorption and reaction sites for reactive oxygen species, enhancing the material's ability to adsorb and scavenge excess reactive oxygen species in the microenvironment of degenerated intervertebral discs. TiCx exhibits excellent electrical conductivity and interfacial electronic modulation capabilities, enabling it to construct a heterogeneous interfacial structure with SrTiOv. This promotes interfacial electron transfer after ultrasonic excitation, reduces electron-hole recombination, and improves the material's ultrasonic response performance.
[0065] The mass ratio of SrTiOv to TiCx is 10:1 to 1:10, preferably 5:1 to 1:5, and more preferably 2:1 to 1:2.
[0066] The particle size of the SrTiOv-TiCx composite material is 20–500 nm, preferably 50–300 nm, and more preferably about 200 nm.
[0067] In this invention, SrTiOv-TiCx is not simply used as a filler, but rather as a functional nanocomponent with an oxygen vacancy structure and ultrasonic response properties. On the one hand, it enhances ROS adsorption and scavenging capacity through oxygen vacancies; on the other hand, it promotes electron transfer through the heterogeneous interface between SrTiOv and TiCx, thereby enhancing the regulatory effect on the microenvironment of degenerated intervertebral discs under ultrasonic stimulation.
[0068] III. Structure and Function of Injectable Hydrogel Matrix This invention utilizes sodium alginate and chitosan to construct a composite hydrogel matrix. Sodium alginate exhibits excellent biocompatibility, hydrophilicity, and ionic crosslinking ability; chitosan possesses excellent biocompatibility, biodegradability, and adhesiveness. The combination of these two materials forms a hydrogel network suitable for local injection into the intervertebral disc.
[0069] The role of the hydrogel matrix in this invention includes: As a local delivery carrier for SrTiOv-TiCx; To improve the retention capacity of functional nanomaterials in the intervertebral disc; Reduce the uncontrollable problems of diffusion, loss, or release of nanomaterials after individual injection; Rapid gelation creates localized support and a slow-release environment; Together with SrTiOv-TiCx, they constitute an injectable and controllable response intervertebral disc degeneration repair system.
[0070] The gelation time of the composite hydrogel is 10 s to 10 min, preferably 30 s to 5 min, and more preferably about 2 min. The gelation temperature is 4 to 45°C, preferably room temperature to 37°C.
[0071] IV. Preparation Method The present invention also provides a method for preparing the above-mentioned ultrasound-responsive injectable composite hydrogel, comprising the following steps: Step S1: Preparation of oxygen-vacancy strontium titanate (SrTiO2) nanomaterials Strontium and titanium sources are added to a solvent and thoroughly stirred to obtain a strontium titanate precursor solution or suspension. Strontium titanate nanomaterials are then prepared by hydrothermal method, sol-gel method, precipitation method or calcination method. The obtained strontium titanate nanomaterials are then subjected to heat treatment in an inert atmosphere, low oxygen atmosphere or reducing atmosphere to form oxygen vacancies, thus obtaining oxygen vacancy strontium titanate SrTiOv nanomaterials.
[0072] The strontium source includes, but is not limited to, one or more of strontium nitrate, strontium chloride, strontium acetate, and strontium carbonate.
[0073] The titanium source includes, but is not limited to, one or more of tetrabutyl titanate, titanium tetrachloride, isopropyl titanate, and titanium dioxide.
[0074] The heat treatment temperature is 300–900℃, preferably 400–800℃; the heat treatment time is 0.5–12 h, preferably 1–6 h.
[0075] The purpose of this step is to obtain strontium titanate nanomaterials with oxygen vacancy structures, enabling them to possess the basis for ROS adsorption and ultrasonic response.
[0076] Step S2: Preparation of TiCx dispersion TiCx material was added to deionized water, ethanol, water / ethanol mixture, PBS buffer or physiological saline, and then ultrasonically dispersed to obtain a uniform TiCx dispersion.
[0077] The TiCx can be titanium carbide powder, titanium carbide nanosheets, Ti3C2Tx MXene, or other two-dimensional titanium carbide materials.
[0078] The concentration of the TiCx dispersion is 0.1–20 mg / mL, preferably 0.5–10 mg / mL, and more preferably 1–5 mg / mL.
[0079] The ultrasonic dispersion time is 5–120 min, preferably 10–60 min.
[0080] The purpose of this step is to uniformly disperse TiCx, which facilitates the subsequent formation of a composite structure with SrTiOv.
[0081] Step S3: Preparation of SrTiOv-TiCx composite material The SrTiOv nanomaterials obtained in step S1 are added to the TiCx dispersion obtained in step S2, and the SrTiOv and TiCx are mixed at a mass ratio of 10:1 to 1:10. The mixture is fully composited for 0.5 to 48 h by magnetic stirring, ultrasonic dispersion, mechanical oscillation or a combination thereof. Then, the mixture is centrifuged, washed and dried to obtain the SrTiOv-TiCx composite material.
[0082] The centrifugation speed is 3000–15000 rpm, and the centrifugation time is 5–30 min. The drying methods include freeze drying, vacuum drying, or low-temperature drying.
[0083] The purpose of this step is to load or bond SrTiOv onto the TiCx surface, forming an SrTiOv-TiCx composite material with a heterogeneous interface structure. This heterogeneous interface can promote electron transfer after ultrasonic excitation, reduce electron-hole recombination, and improve the material's ability to regulate its response to ROS.
[0084] Step S4: Prepare sodium alginate solution Sodium alginate was added to a physiologically acceptable solvent and stirred until completely dissolved to obtain a sodium alginate solution.
[0085] The sodium alginate solution has a mass-volume concentration of 0.5% to 5% w / v, preferably 1% to 3% w / v.
[0086] The stirring temperature is room temperature to 60℃, and the stirring time is 0.5 to 24 h.
[0087] The purpose of this step is to obtain the main network components of the hydrogel.
[0088] Step S5: Prepare chitosan solution Chitosan is dissolved in a weakly acidic aqueous solution to obtain a chitosan solution, and the pH is adjusted to 5.5-7.4, preferably 6.0-7.2.
[0089] The weakly acidic aqueous solution includes, but is not limited to, acetic acid solution, lactic acid solution, or dilute hydrochloric acid solution.
[0090] The chitosan solution has a mass-volume concentration of 0.1% to 3% w / v, preferably 0.3% to 2% w / v, and more preferably 0.5% to 1.5% w / v.
[0091] The purpose of this step is to obtain a natural polysaccharide component that can be combined with sodium alginate to form a gel, thereby improving the stability, adhesion, and biocompatibility of the hydrogel.
[0092] Step S6: Preparation of sodium alginate-chitosan composite hydrogel precursor solution The sodium alginate solution obtained in step S4 is mixed with the chitosan solution obtained in step S5, so that the mass ratio of sodium alginate to chitosan is 10:1 to 1:5, to obtain the sodium alginate-chitosan composite hydrogel precursor solution.
[0093] Mixing methods include magnetic stirring, vortex mixing, mechanical stirring, or repeated push-pull mixing with a syringe. The mixing time is 1–60 min, preferably 5–30 min.
[0094] The purpose of this step is to form a hydrogel precursor system capable of supporting SrTiOv-TiCx.
[0095] Step S7: Loading SrTiOv-TiCx composite material The SrTiOv-TiCx composite material obtained in step S3 is added to the composite hydrogel precursor solution obtained in step S6, so that the final concentration of SrTiOv-TiCx is 1-1000 μg / mL, preferably 10-500 μg / mL, more preferably 50-200 μg / mL, and most preferably 100 μg / mL; the mixture is thoroughly stirred, vortexed or ultrasonically dispersed to ensure that SrTiOv-TiCx is uniformly dispersed in the hydrogel precursor solution.
[0096] The purpose of this step is to uniformly load functional nanomaterials into an injectable hydrogel system, enabling it to have local delivery and sustained action.
[0097] Step S8: Crosslinking into a gel Add a crosslinking agent to the hydrogel precursor system obtained in step S7, or inject it into an environment containing crosslinking ions to induce a crosslinking reaction and form an ultrasonically responsive injectable composite hydrogel loaded with SrTiOv-TiCx.
[0098] The gelation temperature is 4–45°C, preferably room temperature to 37°C; the gelation time is 10 s to 10 min, preferably 30 s to 5 min, and more preferably about 2 min.
[0099] The purpose of this step is to form a composite hydrogel with injectability, local retention and ultrasonic responsiveness.
[0100] V. Usage and Operation Process In use, the sodium alginate-chitosan composite hydrogel precursor system loaded with SrTiOv-TiCx or the pre-formed injectable hydrogel is delivered to the degenerated intervertebral disc via injection, so that it gels or remains in the intervertebral disc.
[0101] Subsequently, ultrasonic stimulation was applied to the injection site. The ultrasonic stimulation frequency was 20 kHz to 3 MHz, and the ultrasonic intensity was 0.1 to 3 W / cm². 2 The duration of ultrasound stimulation is 1–30 minutes. The intensity of ultrasound stimulation can be adjusted according to the severity of the lesion, the concentration of the material, and the clinical operating conditions.
[0102] Under ultrasound, the piezoelectric response and interfacial electron transfer capacity of SrTiOv-TiCx are enhanced, further improving its adsorption and clearance of excess ROS in degenerated intervertebral discs. Reduced ROS levels can further inhibit abnormal activation of the TNF-α / NF-κB / MAPK inflammation-related pathway, decrease the expression of inflammation-related or extracellular matrix degradation-related factors such as P65, p-P65, MMP13, and NLRP3, thereby protecting nucleus pulposus cells, reducing extracellular matrix degradation, and delaying intervertebral disc degeneration.
[0103] VI. Improvements of the present invention compared to the prior art Compared with drug therapy alone, this invention achieves local delivery and retention through injectable hydrogels, reducing the problem of insufficient local action time of drugs or functional materials in the intervertebral disc.
[0104] Compared with ordinary hydrogels, the hydrogel of the present invention not only has filling and delivery functions, but also loads SrTiOv-TiCx composite material with oxygen vacancy structure and ultrasonic response capability, which can actively regulate ROS and inflammatory microenvironment.
[0105] Compared with single antioxidant nanomaterials, the SrTiOv-TiCx in this invention promotes electron transfer and enhances the ROS regulation capability under ultrasonic response by forming a heterogeneous interface between SrTiOv and TiCx.
[0106] Compared with single ultrasound-responsive materials, this invention further loads SrTiOv-TiCx into sodium alginate-chitosan hydrogel, giving it injectable, locally retained, and sustained-action capabilities, making it more suitable for local treatment of intervertebral discs.
[0107] Therefore, this invention solves the problems of low local delivery efficiency of intervertebral disc, insufficient ROS clearance, limited regulation of inflammatory pathways, and insufficient protection of extracellular matrix in the prior art by using a combination of techniques: "oxygen vacancy functional nanomaterials - heterogeneous interface electron transfer - ultrasound response activation - local delivery with injectable hydrogel".
[0108] VII. Explanation of English Abbreviations and Special Codes SrTiOv: Strontium titanate with oxygen vacancy, where v represents oxygen vacancy.
[0109] TiCx: Titanium carbide material, where x indicates that the composition of carbon or surface groups in titanium carbide can vary to some extent.
[0110] SrTiOv-TiCx: Strontium titanate-titanium carbide composite material with oxygen vacancies.
[0111] ST: Abbreviation for SrTiOv-TiCx.
[0112] ROS: Reactive Oxygen Species.
[0113] IVDD: Intervertebral Disc Degeneration.
[0114] NF-κB: Nuclear Factor kappa-B.
[0115] MAPK: Mitogen-Activated Protein Kinase.
[0116] TNF-α: Tumor Necrosis Factor-α.
[0117] ECM: Extracellular Matrix.
[0118] NP cells or NPCs: Nucleus Pulposus Cells.
[0119] MMP13: Matrix Metalloproteinase 13.
[0120] NLRP3: NOD-like receptor thermal protein domain associated protein 3.
[0121] P65: A key subunit in the NF-κB signaling pathway.
[0122] p-P65: Phosphorylated p65, representing an indicator of the activation status of the NF-κB pathway.
[0123] The above embodiments are only used to illustrate the present invention and are not intended to limit the technical solutions described herein. Although the present invention has been described in detail with reference to the above embodiments, the present invention is not limited to the specific embodiments described above. Therefore, any modifications or equivalent substitutions to the present invention, as well as all technical solutions and improvements that do not depart from the spirit and scope of the invention, are covered within the scope of the claims of the present invention.
Claims
1. An ultrasonically responsive oxygen-vacancy strontium titanate-titanium carbide composite material, characterized in that, The composite material is a SrTiOv-TiCx composite structure, which is composed of oxygen-vacancy strontium titanate SrTiOv and titanium carbide TiCx. The SrTiOv has oxygen vacancy active sites, and the SrTiOv and TiCx form a heterogeneous interface structure. The composite material has ultrasonic response characteristics and ROS controllable regulation capability.
2. The ultrasonically responsive oxygen-vacancy strontium titanate-titanium carbide composite material according to claim 1, characterized in that, The mass ratio of SrTiOv to TiCx is 10:1 to 1:10, preferably 2:1 to 1:2; the particle size of the composite material is 20 to 500 nm, preferably 50 to 300 nm; the composite material can enhance interfacial electron transfer, inhibit electron-hole recombination, and improve ROS adsorption and removal efficiency under ultrasonic stimulation.
3. An ultrasound-responsive oxygen-vacancy strontium titanate-titanium carbide composite nanohydrogel, characterized in that, The hydrogel formulation uses sodium alginate-chitosan as the hydrogel matrix and loads the SrTiOv-TiCx composite material as described in claim 1 or 2; the component ratios satisfy: final concentration of SrTiOv-TiCx 1-1000 μg / mL, sodium alginate 0.5%-5% w / v, and chitosan 0.1%-3% w / v; the gelation time of the hydrogel formulation is 10 s-10 min.
4. The ultrasonically responsive oxygen-vacancy strontium titanate-titanium carbide composite nanohydrogel according to claim 3, characterized in that, The final concentration of SrTiOv-TiCx is preferably 100 μg / mL, the concentration of sodium alginate is preferably 1.5% to 2.5% w / v, the concentration of chitosan is preferably 0.5% to 1.5% w / v, and the gelation time of the hydrogel formulation is 2 min under optimized conditions; the mass ratio of sodium alginate to chitosan is 10:1 to 1:5, preferably 3:1 to 1:
1.
5. The ultrasonically responsive oxygen-vacancy strontium titanate-titanium carbide composite nanohydrogel according to claim 3, characterized in that, The hydrogel formulation further comprises a crosslinking agent and a physiologically acceptable solvent; the crosslinking agent has a concentration of 1–500 mmol / L and is selected from one or more of calcium chloride, calcium gluconate, calcium sulfate, sodium β-glycerophosphate, and sodium tripolyphosphate; the physiologically acceptable solvent is one or more of deionized water, PBS buffer, physiological saline, and weakly acidic aqueous solution.
6. The method for preparing the ultrasonically responsive oxygen-vacancy strontium titanate-titanium carbide composite nanohydrogel according to any one of claims 3-5, characterized in that, Includes the following steps: S1. Preparation of oxygen-vacancy strontium titanate SrTiOv: A precursor is prepared by mixing a strontium source and a titanium source. Strontium titanate is then prepared by hydrothermal method / sol-gel method / calcination method. Oxygen vacancies are then constructed by reduction heat treatment to obtain SrTiOv. S2. Preparation of a uniform TiCx dispersion: TiCx material is added to a physiological solvent and dispersed by ultrasonication to obtain a stable TiCx dispersion; S3. Preparation of SrTiOv-TiCx composite material: SrTiOv and TiCx dispersion were mixed in proportion, stirred, ultrasonically compounded, centrifuged, washed and dried to obtain SrTiOv-TiCx composite material; S4. Preparation of sodium alginate-chitosan composite precursor solution: Dissolve sodium alginate and chitosan separately, adjust the pH and mix them in proportion to obtain hydrogel precursor solution. S5. Loading and cross-linking: The SrTiOv-TiCx composite material is added to the precursor solution and dispersed evenly. A cross-linking agent is added for cross-linking, and the mixture is rapidly molded to obtain an injectable composite hydrogel formulation.
7. The preparation method of the ultrasonically responsive oxygen-vacancy strontium titanate-titanium carbide composite nanohydrogel according to claim 6, characterized in that, In step S1, the heat treatment temperature is 300–900℃, the heat treatment time is 0.5–12h, and the heat treatment atmosphere is an inert atmosphere, a low-oxygen atmosphere, or a reducing atmosphere; in step S2, the concentration of TiCx dispersion is 0.1–20 mg / mL, and the ultrasonic dispersion time is 5–120 min; in step S3, the composite reaction time is 0.5–48 h, and the centrifugation speed is 3000–15000 rpm.
8. The application of the ultrasound-responsive oxygen-vacancy strontium titanate-titanium carbide composite nanohydrogel according to any one of claims 1-4 in the treatment of intervertebral disc degeneration, characterized in that, Used to prepare drugs, injectable preparations, sustained-release preparations, or intervertebral disc tissue repair materials for the treatment or repair of intervertebral disc degeneration.
9. The application of the ultrasound-responsive oxygen-vacancy strontium titanate-titanium carbide composite nanohydrogel according to claim 8 in the treatment of intervertebral disc degeneration, characterized in that, The composite material or composite hydrogel formulation achieves targeted therapeutic intervention under the action of ultrasound. The specific mechanisms of action include: clearing excess ROS in the intervertebral disc degeneration microenvironment, regulating the NF-κB / MAPK inflammatory signaling pathway, and reducing the expression of P65, p-P65, MMP13, and NLRP3 proteins.
10. The application of the ultrasound-responsive oxygen-vacancy strontium titanate-titanium carbide composite nanohydrogel according to claim 9 in the treatment of intervertebral disc degeneration, characterized in that, The composite material or composite hydrogel formulation achieves repair effects such as macrophage M1-to-M2 polarization, nucleus pulposus cell protection, ECM degradation inhibition, and delaying the progression of intervertebral disc degeneration by regulating the inflammatory microenvironment.